The Phenomenological study of Safety Management of Nursing Organization at Advanced-Level Hospitals under the Ministry of Public Health - เสียงอ่อน ลัดดาวรรณ; ศรีทุมมา เนตรชนก; มีหาญพงษ์ ปราณี (Journal of The Royal Thai Army Nurses, 2018)
This research study is a qualitative study with the objective for phenomenological study of the safety management of nursing organization at advanced-level hospitals under the Ministry of Public Health. The collected data were analyzed through the review of the literature, and were subsequently used to synthesize the framework and to further develop measuring tools for safety management according to the conceptual framework of International Civil Aviation Organization (ICAO) and the research study of Sammer E. Christine. Data were collected from nine nursing managers from nursing departments at advanced-level hospitals with experience in hospital safety’s quality assurance or management. The research tool was a set of semi-structured, in-depth interview with three open-ended questionnaires. The recorded conversations during the interviews were then analyzed word-by-word and the significant statement were categorized according to the relationship of extracted words. The content validity index (IOC) was 0.83 and the Content Validity Index (CVI) was 0.91. The study found that there were six factors that should be incorporated into the safety management model of nursing organization at advanced-level hospitals under the Ministry of Public Health. Which are listed as follow: 1) Safety policy and objectives 2) Safety risk management 3) Safety assurance 4) Safety promotion 5) Teamwork and 6) Leadership. The findings of this study should be guide Such elements will help the nursing executives used to manage safety more effectively. Findings from this research were used as a guideline for developing the safety management system of the nursing organization. This is also the basic information for the policy formulation in the safety management of all nursing departments under the nursing organization at advanced-level hospitals under the Ministry of Public Health.